The spectrum of functional, structural, and patient-reported outcomes in intermediate age-related macular degeneration: a MACUSTAR study report - Terheyden, Jan H.; Holz, Frank G.; Behning, Charlotte; Dunbar, Hannah M.P.; Schmitz-Valckenberg, Steffen; Tufail, Adnan; Schmid, Matthias; Crabb, David P.; Saßmannshausen, Marlene; Binns, Alison; Hoyng, Carel B.; Zakaria, Nadia; et al. (Ophthalmologica, 2025)
Introduction: There is an unmet medical need for therapies in intermediate age-related macular degeneration (iAMD). The prospective European multicenter cohort study MACUSTAR validates structural, functional, and patient-reported iAMD endpoints for use in future trials. The multiplicity of assessments allows characterizing iAMD in more dimensions than previously available. We describe the heterogeneity of assessments in the iAMD baseline cohort of the MACUSTAR study. Methods: A wide range of assessments was administered across 20 European study sites in accordance with established guidelines. These assessments encompassed multiple structural evaluations, such as color fundus photography, fundus autofluorescence, and optical coherence tomography. Additionally, functional tests were conducted, including assessments of best-corrected and low-luminance visual acuity (VA), Moorfields acuity, contrast sensitivity, reading speed, mesopic and scotopic microperimetry, and dark adaptometry. Moreover, patient-reported outcome assessments, specifically the Vision Impairment in Low Luminance questionnaire, were also incorporated into the evaluation process. Associations between variables were investigated using Phi coefficients, Pearson correlation coefficients and age-corrected regression models. Results: Five-hundred eighty-five individuals with iAMD (66% women; mean (standard deviation) age: 72 ± 7 years) were included in the MACUSTAR study. Forty-nine percent had pigmentary abnormalities, 27% had reticular pseudodrusen; 10% and 9% had incomplete and complete retinal pigment epithelium and outer retinal atrophy at baseline, respectively. Mean best-corrected VA, low-luminance VA and mesopic average threshold on microperimetry at baseline were 0.03 ± 0.11 logMAR, 0.24 ± 0.16 logMAR, and 23.3 ± 3.7 dB. Mean Vision Impairment in Low Luminance (VILL) subscale scores at baseline were 2 ± 2 to 2 ± 3 logits. Phi coefficients between structural assessments ranged between 0.17 and 0.22 (median 0.21); correlation coefficients between function tests ranged between 0.07 and 0.69 (median 0.34) and between VILL scores ranged between 0.21 and 0.68 (median 0.23). Conclusion: The findings from this broad and comprehensive spectrum of assessments of structure, function, and patient-reported outcomes in iAMD suggest that the disease spectrum is diverse and heterogeneous and that further efforts are necessary to fully understand and characterize iAMD in all its complexities. A further in-depth characterization will enable novel enrichment strategies for clinical trials in iAMD.
Online veröffentlicht: 3. Februar 2025
Gesehen am 01.07.2025